Double-trap model for hysteretic current-voltage characteristics of a polystyrene/ZnO nanorods stacked layer. (November 2017) - Wu, You-Lin; Lin, Jing-Jenn; Lin, Shih-Hung; Sung, Yi-Hsing
Highlights: Clockwise hysteretic I-V is observed in a Ti/PS/ZnO nanorods/FTO device. The hysteretic I-V follows the SCLC conduction plus the Poole-Frenkel emission. A double-trap model is proposed to describe the clockwise hysteretic I-V behavior. Abstract: Hysteretic current-voltage (I-V) characteristics are quite common in metal-insulator-metal (MIM) devices used for resistive switching random access memory (RRAM). Two types of hysteretic I-V curves are usually observed, figure eight and counter figure eight (counter-clockwise and clockwise in the positive voltage sweep direction, respectively). In this work, a clockwise hysteretic I-V curve was found for an MIM device with polystyrene (PS)/ZnO nanorods stack as an insulator layer. Three distinct regions I ∼ V, I ∼ V 2, and I ∼ V 0.6 are observed in the double logarithmic plot of the I-V curves, which cannot be explained completely with the conventional trap-controlled space-charge-limited-current (SCLC) model. A model based on the energy band with two separate traps plus local energy variation and trap-controlled SCLC has been developed, which can successfully describe the behavior of the clockwise hysteretic I-V characteristics obtained in this work.